Review of Violent Intimacies: The Trans Everyday and the Making of an Urban World by Aslı Zengin (Duke University Press) - Avik Sarkar (Lateral)
Aslı Zengin’s Violent Intimacies theorizes the fraught encounter between the Turkish state and its trans subjects. Introducing the analytic framework of “violent intimacies,” Zengin advances two main claims: structural violence unfolds through intimate contact with gendered bodies, and trans women, in turn, confront this violence with intimate practices of resistance. Zengin’s work marks a significant intervention within trans studies. She pays close attention to the materiality of the body as the location where violence is both enacted and contested—a welcome departure from the tendency towards abstraction in trans theoretical production. She also pushes the field in transnational directions to address experiences of gender transgression beyond North America and Western Europe. A rich ethnography of trans life in Turkey, the text depicts everyday scenes of violent intimacies across several interpersonal and institutional settings: the street, police, medicine, law, and family. Violent Intimacies offers a vibrant account of Turkish trans women who—faced with state neglect and social exclusion—envision alternative ways of building worlds and sustaining life.